The case of the unusual progression of the left atrial malignant tumor - R.M. Vitovsky; V.V. Isaenko; O.A. Pishchurin; V.F. Onishchenko; O.Z. Paratsiy; I.G. Yakovenko; D.N. Dyadyun; T.I. Dedkova (Кардіохірургія та інтервенційна кардіологія)
The article presents the clinical case of the 22-year old patient with malignant tumor of the left atrium. The character and size of the tumor were distinguished only during surgery. This case has a practical value from point of view of the complicated diagnosis, as well as special surgical treatment and unpredictability of the tumor macrostructure. Laboratory and instrumental diagnostic methods were used, including transthoracic and transesophageal B-mode color Doppler echocardiography, which made possible to detect the tumor. After successful surgical treatment of the tumor a patient was discharged at 12 days in satisfactory condition.